Creating a Safer Financial System : Will the Volcker, Vickers, and Liikanen Structural Measures Help? - Vinals, Jose (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
The U.S., the U.K., and more recently, the E.U., have proposed policy measures directly targeting complexity and business structures of banks. Unlike other, price-based reforms (e.g., Basel 3 and G-SIFI surcharges), these proposals have been developed unilaterally with material differences in scope, design and implementation schedules. This may exacerbate cross-border regulatory arbitrage and put a further burden on consolidated supervision and cross-border resolution. This paper provides an analysis of the potential implications of implementing different structural policy measures. It proposes a pragmatic and coordinated approach to development of these policies to reduce risk of regulatory arbitrage and minimize unintended consequences. In doing so, it also aims to identify a set of common policy measures that countries could adopt to re-scope bank business models and corporate structures.